Parliamentary English Debate Within Communicative Language Teaching Context: A Personal Reflection - Erwin Suhendra (EDULANGUE, 2020)
This paper discusses further contributions of English debate within the Communicative Language Teaching framework (therefore CLT). In the English as a Foreign Language classrooms (henceforth EFL), presentation remains the prominent instructional strategy, which does not accommodate learners’ English skills and critical thinking skills development in a more engaging, interactive and critical way. Parliamentary English debate as an interactive instructional strategy has been found to mediate the aforementioned skills and the macro skills being learnt such as reading, speaking, listening and writing. However, there has been a death of scholarly discussion on the English debate’s contributions framed under the CLT. For this reason, this paper tries to shed lights on how the parliamentary English debate and its contributions to EFL learners in the CLT sphere. Debating as a teaching strategy does not only serve purposes for the students’ language skills development but also promote their critical thinking skills and self- confidence.